Failure Mechanisms and Risk-Based Mitigation of Hydrocarbon Pipeline Blockages: A Comprehensive Review - Hamdani Wahab; Asral; Awaludin Martin (Testing Center for Oil and Gas LEMIGAS, 2026)
Hydrocarbon pipelines play a vital role in ensuring the continuous transportation of oil and gas. However, pipeline blockages remain a major operational challenge because of their significant impacts on safety, environmental protection, and production reliability. This study presents a literature review aimed at identifying and classifying the hazards and risks associated with hydrocarbon pipeline blockages using a 5×5 risk matrix based on the MIL-STD-882B military safety standard. Historical incident data from 1970–2024 were collected from the Pipeline and Hazardous Materials Safety Administration of the US Department of Transportation to support the risk assessment process. The analysis indicates that environmental damage is the most significant consequence of pipeline blockage incidents (28%), followed by fire and explosion (22%), toxic gas exposure (17%), overpressure (13%), economic losses (11%), and production losses (9%). Furthermore, environmental recovery costs account for approximately 88.6% of the total financial impact, while the probability of severe incidents reaches 80%, with estimated economic losses up to USD 20 million or production disruptions of 25%. The findings highlight the urgent need for effective mitigation and prevention strategies to improve pipeline integrity, operational safety, and sustainability within the oil and gas industry.